Proposed Improvement of Monitoring and Controlling Process on Outstanding Customer (Study Case: XYZ Company in Jambi Area) - Asih Aulia Putri; Heriyono Lalu; Sri Widaningrum (International Journal of Innovation in Enterprise System, 2022)
PT XYZ is a company that provides telecommunications services, and for corporate customers, there is the BGES Unit. The payment process for corporate customers is managed by one of the BGES pillars, namely Collection Management. One of the tasks that Collection Management takes care of is outstanding data. The achievement of outstanding billing is only 14.75% per year, which means a payment delay of IDR 7,000,458,871.00 in 2021. Due to excessive workload, billing management does not supervise customers regarding billing so billing objectives are not achieved. In addition, billing information in the form of invoices is provided later than the 5th through 12th of each month so that customers do not know for sure the total bill. This research aims to make improvements in the monitoring and controlling processes of customer outstanding billing. This research uses the business process improvement method. This method also refers to a process that works but some activities need improvement. It does not design new activities but improves existing activities. The tools of business process improvement that were used in this research are application technique wheels and streamlining, which can be useful for simplifying a process and fixing a problem based on the outstanding billing problems by PT XYZ. The result of this research is a new business process as is dashboard monitoring and controlling shown by a context diagram that contains incoming and outgoing data on the billing information system and reminder notification will appear if the target is not achieved. The new business process is expected to assist the BGES unit in monitoring and controlling customers every month, and the target that is expected to be achieved is an outstanding figure of less than 1,000,000 by the end of the year.